2019
DOI: 10.3390/su12010099
|View full text |Cite
|
Sign up to set email alerts
|

CEO Tenure, Corporate Social Performance, and Corporate Governance: A Korean Study

Abstract: The purpose of this study was to examine the association between Chief Executive Officer (CEO) tenure and corporate social performance with the moderating effect of governance. We investigated whether new CEOs and CEOs in their last year of service were more focused on short-termism than CEOs of other periods. Specifically, we tested whether these CEOs reduced social performance that demands immediate expenditure and expect payoffs in the long run. We also tested whether good governance can mitigate such behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…This intangible asset could be subdivided into classes relating to each of the three main themes of CSR (Park et al 2020): the social reputation of the employer on well-being at work; societal reputation with regard to stakeholders (customers, consumers, local communities, subcontractors); environmental reputation (Chyz et al 2019;Choi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This intangible asset could be subdivided into classes relating to each of the three main themes of CSR (Park et al 2020): the social reputation of the employer on well-being at work; societal reputation with regard to stakeholders (customers, consumers, local communities, subcontractors); environmental reputation (Chyz et al 2019;Choi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This study also observed the level of tenure and frequency of CEO meetings with corporate CSR disclosures. Referring to previous research [70][71][72], CEO tenure can be classified into several levels to clarify the results. In this analysis, CEO tenure was classified into two segments based on median value, namely 'long tenure' if the value was below the median (LONGER_TENURE) and 'very long tenure' if the value was above the median.…”
Section: Additional Analysismentioning
confidence: 99%
“…The years a CEO works as a corporate governance pillar affects CSR disclosure and financing decisions, including debt financing. Extant literature has examined CEO tenure and debt financing or CEO tenure and CSR disclosure (Choi et al. , 2020; Naseem et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2016). Studies have also focused on how corporate governance principles such as chief executive officer (CEO) tenure affect the pursuance of CSR activities (Tarus and Ayabei, 2016; Choi et al. , 2020; Kaur and Singh, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation